Efeito do dimorfismo sexual e da fenologia no desempenho ecofisiológico de uma espécie dioica (Myrsine coriacea) na Floresta Atlântica - Valente, Cecília Silva (2017)
The sexual dimorphism in secondary characteristics, evidenced in some dioecious species, allows individuals to have strategies of allocation and use of resources according to the specific demand of each sex, increasing thus the ability to explore limiting environments. Females generally show greater carbon investment during reproductive development, due to fruit production. Males have a higher nutritional demand for the production of pollen. The aim of work was to assess the effects of the sexual dimorphism and of the phenological phases on ecophysiological performance between male and female trees of M. coriacea from nine populations.The functional characteristics measured were related to growth, biomass partition, chemical composition of leaf tissue and photosynthetic efficiency.In general, there was sexual dimorphism in the echophysiological performance. However, the effect of sexual dimorphism was dependent on the phenological phase and the environmental conditions of each population. Sexual dimorphism was observed in functional characteristics only during the flowering and fruiting phases.The performance of males was associated with the maintenance of higher growth rates, while female performance was related to higher contents of chloroplastidic pigments and greater photosynthetic efficiency.The results showed that the specie presented a combination of changes in functional characteristics (functional diversity),as way of responding to the different demands of resources at the individual level.The less competition for resources, favors the coexistence of the sexes and maximizes the exploitation of the resources of the environment, as a way to enhance the reproductive success of the species.